2018
DOI: 10.1021/acs.est.7b05464
|View full text |Cite
|
Sign up to set email alerts
|

New Insights to Compare and Choose TKTD Models for Survival Based on an Interlaboratory Study for Lymnaea stagnalis Exposed to Cd

Abstract: Toxicokinetic-toxicodynamic (TKTD) models, as the General Unified Threshold model of Survival (GUTS), provide a consistent process-based framework compared to classical dose-response models to analyze both time and concentration-dependent data sets. However, the extent to which GUTS models (Stochastic Death (SD) and Individual Tolerance (IT)) lead to a better fitting than classical dose-response model at a given target time (TT) has poorly been investigated. Our paper highlights that GUTS estimates are general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…The goodness-of-fit of the GUTS models was slightly smaller than that of the dose-response model. This difference was possibly due to the deviation between the observed and fitted values, which was mainly caused by the dominant parameters of the GUTS model (K d , Z, or α) that had been correlated for laboratories and had an influence on the survival rate over time (Baudrot et al 2018 FIGURE 4: Comparison of the observed and fitted values by using different general unified threshold (GUTS) models with different levels of cadmium (Cd) and lead (Pb). (A) GUTS-stochastic death (SD) exposed to Cd.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The goodness-of-fit of the GUTS models was slightly smaller than that of the dose-response model. This difference was possibly due to the deviation between the observed and fitted values, which was mainly caused by the dominant parameters of the GUTS model (K d , Z, or α) that had been correlated for laboratories and had an influence on the survival rate over time (Baudrot et al 2018 FIGURE 4: Comparison of the observed and fitted values by using different general unified threshold (GUTS) models with different levels of cadmium (Cd) and lead (Pb). (A) GUTS-stochastic death (SD) exposed to Cd.…”
Section: Discussionmentioning
confidence: 99%
“…The GUTS models had a greater ability than the dose-response model to predict toxicity. Moreover, the dose-response model is empirical, with no information on mechanisms of toxic action, whereas the GUTS model incorporates some mechanistic understanding (Brock et al 2010;Baudrot et al 2018). The current paradigm of GUTS for most metals is spillover, in which metals are bound by metal-binding proteins to a threshold, above which free metals spill over into the cell and cause toxicity (Morcillo et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the GUTS-RED-IT model is based on the critical body residue (CBR) approach, which assumes that individuals differ in their thresholds, following a probability distribution, and die as soon as the internal concentration reaches the individualspecific threshold [29]. The robustness of GUTS models in calibration and prediction has been widely demonstrated, with little difference between GUTS-RED-SD and GUTS-RED-IT models [7,10,30]. Sensitivity analysis of toxicity endpoints derived from GUTS models, such as LC(x, t) and M F (x, t), has also been investigated [7,10], but the question of how uncertainties are propagated is still under-studied.…”
Section: Introductionmentioning
confidence: 99%